Barriers of knowledge sharing in Malaysian hotels - Freydouni, Shahrbanoo Gholipour; Woods, Peter (2010)
The purpose of this research is to identify the important barriers in knowledge sharing in luxury hotels and consider significance of motivational points for managers in using knowledge sharing base on knowledge management strategy for their requirement, in Kuala Lumpur, Malaysia.This qualitative research was selected through 23 persons semi-structured interviews with managers and some senior staff of three (four-five) hotels in Malaysia.The progressive comparative analysis was applied in this article.The result shows that barriers in work environment, personnel attitude, and knowledge transfer within the organization, are the main barriers observed in luxury hotels in Malaysia.Identifying the barriers of sharing knowledge and overcoming them in hotel industry of Malaysia as a tourism country can help the stakeholders in this industry to increase the organizational capability and effectiveness, and gain more intellectual assets in terms of knowledge as their competitive advantages.